SDF‐1α (Stromal Cell‐Derived Factor 1α) Induces Cardiac Fibroblasts, Renal Microvascular Smooth Muscle Cells, and Glomerular Mesangial Cells to Proliferate, Cause Hypertrophy, and Produce Collagen. Issue 11 (7th November 2017) - Jackson, Edwin K.; Zhang, Yumeng; Gillespie, Delbert D.; Zhu, Xiao; Cheng, Dongmei; Jackson, Travis C.
Abstract : Background: Activated cardiac fibroblasts (CFs), preglomerular vascular smooth muscle cells (PGVSMCs), and glomerular mesangial cells (GMCs) proliferate, cause hypertrophy, and produce collagen; in this way, activated CFs contribute to cardiac fibrosis, and activated PGVSMCs and GMCs promote renal fibrosis. In heart and kidney diseases, SDF‐1α (stromal cell‐derived factor 1α; endogenous CXCR4 [C‐X‐C motif chemokine receptor 4] receptor agonist) levels are often elevated; therefore, it is important to know whether and how the SDF‐1α/CXCR4 axis activates CFs, PGVSMCs, or GMCs. Methods and Results: Here we investigated whether SDF‐1α activates CFs, PGVSMCs, and GMCs to proliferate, hypertrophy, or produce collagen. DPP4 (dipeptidyl peptidase 4) inactivates SDF‐1α and previous experiments show that growth‐promoting peptides have greater effects in cells from genetically‐hypertensive animals. Therefore, we performed experiments in the absence and presence of sitagliptin (DPP4 inhibitor) and in cells from normotensive Wistar–Kyoto rats and spontaneously hypertensive rats. Our studies show (1) that spontaneously hypertensive and Wistar–Kyoto rat CFs, PGVSMCs, and GMCs express CXCR4 receptors and DPP4 activity; (2) that chronic treatment with physiologically relevant concentrations of SDF‐1α causes concentration‐dependent increases in the proliferation (cell number) and hypertrophy ( 3 H‐leucine incorporation) of and collagen production ( 3 H‐proline incorporation) by CFs, PGVSMCs, and GMCs; (3) that sitagliptin augments these effects of SDF‐1α; (4) that interactions between SDF‐1α and sitagliptin are greater in spontaneously hypertensive rat cells; (5) that CXCR4 antagonism (AMD3100) blocks all effects of SDF‐1α; and (6) that SDF‐1α/CXCR4 signal transduction likely involves the RACK1 (receptor for activated C kinase 1)/Gβγ/PLC (phospholipase C)/PKC (protein kinase C) signaling complex. Conclusions: The SDF‐1α/CXCR4 axis drives proliferation and hypertrophy of and collagen production by CFs, PGVSMCs, and GMCs, particularly in cells from genetically hypertensive animals and when DPP4 is inhibited.